Quantitative comparison of cortical and deep grey matter in pathological subtypes of unilateral cerebral palsy - Scheck, S.; Pannek, K.; Fiori, S.; Boyd, Roslyn; Rose, S. (2014)
© 2014 Mac Keith Press. Aim: The aim of this study was to quantify grey matter changes in children with unilateral cerebral palsy (UCP), differentiating between cortical or deep grey matter (CDGM) lesions, periventricular white matter (PWM) lesions, and unilateral and bilateral lesions. Method: In a cross-sectional study we obtained high resolution structural magnetic resonance images from 72 children (41 males, 31 females, mean age 10y 9mo [SD 3y 1mo], range 5y 1mo-17y 1mo) with UCP (33 left, 39 right hemiplegia; Manual Ability Classification System level I n=29, II n=43; Gross Motor Function Classification System level I n=46, II n=26), and 19 children with typical development (CTD; eight males, 11 females, mean age 11y 2mo [SD 2y 7mo], range 7y 8mo-16y 4mo). Images were classified by lesion type and analyzed using voxel-based morphometry (VBM) and subcortical volumetric analysis. Results: Deep grey matter volumes were not significantly different between children with CDGM and PWM lesions, with the thalamus, putamen, and globus pallidus being reduced unilaterally in both groups compared with CTD (p=0.001). Children with CDGM lesions additionally showed widespread cortical changes involving all lobes using VBM (p<0.01). Children with bilateral lesions had reduced thalamus and putamen volumes bilaterally (p<0.001). The thalamic volume was reduced bilaterally in children with unilateral lesions (p=0.004). Interpretation: Lesions to the PWM cause secondary changes to the deep grey matter structures similar to primary changes seen in CDGM lesions. Despite having a unilateral phenotype, grey matter changes are observed bilaterally, even in children with unilateral lesions.